Staphylococcus Strains in Atopic Dermatitis in Children: Toxins Production and Resistance Properties - Asya Kudryavtseva; Fyodor Fluer; Lusine Khachatryan; Svetlana Makarova; Oksana Osipenko; Elena Ryzhii; Sergei Titarev; Denis Zaslavsky; Katerina Gelezhe (Life)
Staphylococcus spp. skin colonization is involved in the pathogenesis of atopic dermatitis (AD). While coagulase-positive Staphylococcus aureus strains are known to worsen symptoms, the role of coagulase-negative staphylococci (CoNS) remains controversial. Further research is needed to clarify the pathogenicity of CoNS in AD patients. A study involving 329 children with AD (mean age: 4.89 years) assessed the frequency of staphylococcal colonization on affected skin, along with the toxin-producing properties and antibiotic resistance of isolated strains. Mild AD: Predominantly colonized by CoNS (especially S. epidermidis). Moderate/Severe AD: Showed a significant increase in S. aureus colonization. CoNS (including S. epidermidis) could produce enterotoxins (A, B, C) and toxic shock syndrome toxin-1 (TSST-1), though less frequently than S. aureus strains. In severe AD, the number of toxin-producing CoNS strains (especially enterotoxin A producers) was higher than in mild AD, and the number of non-toxin-producing strains was lower. CoNS exhibited higher resistance rates than S. aureus. Methicillin-resistant S. epidermidis (MRSE): 23.4%. Methicillin-resistant S. aureus (MRSA): 1.27%. CoNS may contribute to AD pathogenesis through toxin production (exacerbating inflammation) and antibiotic resistance (limiting treatment options). Severe AD may involve a synergistic effect between S. aureus and toxin-producing CoNS.